A Case of Oculocutaneous Albinism in a Patient with Hashimoto's Thyroiditis. Issue 1 (16th January 2019) - de Gennaro, Giovanni; Vitti, Paolo; Marinò, Michele
Abstract : Background: Oculocutaneous albinism (OCA) is a heterogeneous autosomal recessive disorder characterized by reduced or absent melanin synthesis. Its prevalence is approximately one in 17, 000 individuals worldwide. OCA causes a complete or partial absence of pigment in the skin, hair, and eyes. Reduction of melanin in the eyes results in reduced visual acuity, photophobia, and nystagmus. To our knowledge, the coexistence of albinism and thyroid autoimmune diseases has not been reported. Case Report: A 37-year-old male with OCA came to our observation for a familial history of autoimmune thyroiditis. He complained with mild asthenia. His brother was affected by OCA and autoimmune thyroiditis. Physical examination revealed the presence of fair skin, platinum white hair, and hypopigmentation of the iris. Laboratory data revealed the presence of subclinical hypothyroidism with positive serum anti-thyroid antibodies. Neck ultrasonography showed a markedly heterogeneously hypoechoic pattern of the thyroid, with a honeycomb-like appearance. Discussion: In the majority of cases, OCA in Caucasians is caused by mutations in the tyrosinase gene. The tyrosinase peptide is normally expressed on the surface of melanocytes, although recent studies have shown its presence in thyroid follicular epithelial cells of patients with Hashimoto's thyroiditis. Therefore, although the mechanism is unclear, the present case report may suggest a pathogenetic link between OCA and Hashimoto's thyroiditis.